Oral Ulcers Caused by Alendronate use - Hakan Cinemre,; Cemil Bilir,; Feyzi Gökosmanoğlu,; Necip Ö. Aytuğ, (Archives of Rheumatology, 2008)
Bisphosphonates are the drugs which modulate bone turnover and reduce bone reabsorbsion. Hence, they are used in postmenopausal osteoporosis , multiple myeloma or osteolisis associated with malign cancer. The rare complications are appearing more often now because of their wide use in treatments. Most important possible adverse effects belong to gastrointestinal systems; esophagitis, gastric ulcers, dyspepsia, heartburn and rarely oral ulcers, osteonecrosis on jaws and esophagial stricturs are illustrated (Rheumatism 2008 23: 35-7)